Behavioral Characteristics and Injection Practices Associated with Skin and Soft Tissue Infections among People who Inject Drugs: A Community-Based Observational Study. Issue 1 (January 2017) - Dahlman, Disa; Håkansson, Anders; Kral, Alex H.; Wenger, Lynn; Ball, Elizabeth L.; Novak, Scott P.
Background : People who inject drugs (PWID) are at increased risk for bacterial skin and soft tissue infections (SSTIs). Although SSTIs pose significant health risks, little is known about their prevalence and characteristics in the population of PWID in the United States. This study investigates whether behavioral factors related to skin and equipment hygiene and tissue-damaging injection practices are associated with recent SSTIs among PWID. Methods : Active PWID were recruited using targeted sampling in San Francisco in 2011–2013. Interviewers collected information on behavioral risk factors of past-month self-reported SSTIs. Inferential analyses used multivariate logistic regression methods (i.e., generalized linear model) to characterize risk factors for past-month SSTIs. Results : The self-reported prevalence of lifetime, past-year, and past-month SSTI was 70%, 29%, and 11%, respectively. Several factors were significantly associated with past-month SSTIs in bivariate analysis, including injecting nonpowder drugs (odds ratio [OR] = 3.57; 95% confidence interval [CI] = 1.23, 10.35; P = .01), needle-licking before injection (OR = 3.36; 95% CI = 1.28, 8.81; P = .01), injecting with someone else's preused syringe/needle (OR = 7.97; 95% CI = 2.46, 25.83; P < .001), being injected by another person (OR = 2.63; 95% CI = 1.02, 6.78; P = .04), infrequent skin cleaning before injection (OR = 2.47; 95% CI = 1.00, 6.10; P = .04), and frequent injections ( P = .02). In multivariate analysis, only syringe/needle sharing (adjusted OR = 6.38; 95% CI = 1.90, 21.46) remained statistically significant. Conclusion : SSTIs are common among PWID. These data highlight the importance of clinical and public health screening efforts to reduce SSTIs. Needle exchange programs may be good venues for SSTIs screening and treatment.